STRENGTHENING PANCASILA AS NATIONAL IDEOLOGY TO IMPLEMENTATE THE BALANCING VALUES TO IMPROVE LAW’S APPLICATION IN INDONESIA - Muhammad Chairul Huda (UNISSULA, 2018)
People’s perception of Pancasila seems to be on the way back. It reminds us that the acceptance of Pancasila as the national ideology is actually not something taken for granted. For that reason, it is necessary to refresh the Pancasila from aspects of knowledge, understanding and practice of the philosophical values contained in it. Law development must be started from the values of Pancasila, because essentially Pancasila is a milestone of convergence of ideas and thoughts on the basic philosophy of state discussed deeply by the founders of the state. Pancasila becomes a sublime agreement (modus vivendi) which is then established as the foundation of state ideology. In this case, Pancasila becomes the rational basis of assumptions about the law to be established as well as the orientation that shows where the nation and state should be established. Thus, Pancasila is an agreement and consensus to build a nation of one country, without considering the different backgrounds that include religion, race, ethnicity, culture, language and others. As the foundation of the state, Pancasila becomes the rechtsidee that should be written in every law-making and enforcement.